Methodological proposal for the teaching-learning process of algebra in the first year of the university (Revista Científica Estelí, 2019)
The general objective of this research was to present a methodological proposal to help students achieve significant learning of the contents in the Algebra unit as part of the General Mathematics course. This study was carried out in the first years of two races of the FAREM-Estelí, UNITE-Managua, in the period 2016-2017. The research process started with a documentary review on the subject of research, which allowed to carry out the necessary theoretical foundation. Subsequently, data were collected through class observation, a survey to students in the selected groups, as well as focal groups, interviews with administrative staff, and teachers. These applied research techniques allowed the collection of data that were then categorized and processed to proceed to the analysis of results. The practical contribution of this thesis is the elaboration of a methodological proposal so that students achieve a better understanding of the Algebra. In the same way, this proposal can be used by the teachers who teach General Mathematics.